2012
DOI: 10.3390/rs4041046
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Coupled System: Multi-Resolution Remote Sensing in Assessing Social-Ecological Responses during 25 Years of Gas Field Development in Arctic Russia

Abstract: Abstract:Hydrocarbon exploration has been underway in the north of West Siberia for several decades. Giant gas fields on the Yamal Peninsula are expected to begin feeding the Nord Stream pipeline to Western Europe in late 2012. Employing a variety of high-to very high-resolution satellite-based sensors, we have followed the establishment and spread of Bovanenkovo, the biggest and first field to be developed. Extensive onsite field observations and measurements of land use and land cover changes since 1985 have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 17 publications
0
56
0
Order By: Relevance
“…Such changes occupy only a minor fraction of NWS and often could be collocated with natural or anthropogenic disturbances of the vegetation cover. This observation lead Macias-Fauria et al (2012) and Kumpula et al (2012) to hypothesize that those disturbances help to establish alternative, more productive ecosystems of graminoids, shrubs and tree seedlings. In this discussion, we consider the major climatological and physical factors that may support the alternative vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such changes occupy only a minor fraction of NWS and often could be collocated with natural or anthropogenic disturbances of the vegetation cover. This observation lead Macias-Fauria et al (2012) and Kumpula et al (2012) to hypothesize that those disturbances help to establish alternative, more productive ecosystems of graminoids, shrubs and tree seedlings. In this discussion, we consider the major climatological and physical factors that may support the alternative vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
“…The development has left significant footprints on the vegetation cover. These footprints were found not only at the development sites but also across large distances (Walker et al, 2009;Kumpula et al, 2012). More specifically, Kumpula et al (2011) reported extensive transformation from shrub-to more productive (greener) grass-and sedge-dominated tundra in NWS that reclaim artificial terrain disturbances at Bovanenkovskiy gas field, Yamal peninsula (70 • N).…”
Section: Introductionmentioning
confidence: 94%
“…Changes may have occurred over this time period, like for instance in areas of gas and oil extraction [42]. This leads to an increase of urban settlements and locally double bounce effects, respectively, which are currently not considered.…”
Section: Sentinel-1 Frozen Surface Backscatter Statisticsmentioning
confidence: 99%
“…Summaries of some of the cumulative effects have been addressed in Russia (Forbes et al, 2009;Walker et al, 2011;Kumpula et al, 2012), Alaska Orians et al, 2003), and globally (AMAP, 2010). Summaries of some of the cumulative effects have been addressed in Russia (Forbes et al, 2009;Walker et al, 2011;Kumpula et al, 2012), Alaska Orians et al, 2003), and globally (AMAP, 2010).…”
Section: Cumulative Effects Of Oil Developmentmentioning
confidence: 99%